2008
DOI: 10.1111/j.1447-0756.2008.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian large cell neuroendocrine carcinoma

Abstract: Ovarian large cell neuroendocrine carcinoma (LCNC) is a rare disease that is commonly associated with a surface epithelial and germ cell neoplasm component. A 46-year-old woman presented with a pelvic mass measuring 15 cm in diameter. She underwent an exploratory laparotomy with resection of the pelvic mass. Diffuse and nodular intra-abdominal disseminations were observed. Stage III LCNC associated with squamous differentiation alone of the right ovary was diagnosed. The patient died of progressive disease 4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…This extremely rare clinical presentation of a huge mass arising from an anatomically normal ovary confirmed laparoscopically, 9 months back was reiterating the fact that this tumour was rapidly growing. Some authors have similar opinion [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 82%
“…This extremely rare clinical presentation of a huge mass arising from an anatomically normal ovary confirmed laparoscopically, 9 months back was reiterating the fact that this tumour was rapidly growing. Some authors have similar opinion [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 82%
“…Immunohistochemistry revealed that the cells of the poorly differentiated component were diffusely positive for CD56, chromogranin A, synaptophysin and NSE. Taken together, the tumor fulfilled the histopathological criteria for a neuroendocrine carcinoma …”
Section: Discussionmentioning
confidence: 86%
“…However, there exist no generally accepted criteria for neuroendocrine tumor differentiation, which usually depends on a combination of typical structural, immunohistochemical and ultrastructural findings. World Health Organization (WHO) criteria describe that LCNEC of the lung is characterized by positive immunostaining for chromogranin A, synaptophysin or CD56 (N‐CAM) and at least one of them is enough if the staining is clear cut . LCNEC of the ovary is very rare and only 35 cases have been reported previously worldwide .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal chemotherapy regimen for LCNECs has not been established. Regimens used for LCNECs are cisplatinum-based chemotherapy or paclitaxel-carboplatin based chemotherapy [9,10]. Patients usually follow an extremely lethal outcome.…”
Section: Discussionmentioning
confidence: 99%